Planning and Evaluation of Hypertension Treatment Program with Precede-Proceed Approach in Tanjungharjo Village, Bojonegoro Regency, East Java, Indonesia - Maurilla Shafira Putri; Erni Astutik (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2023)
Background: Bojonegoro Regency is among the 10 regencies/cities with most hypertension in East Java. Similar condition occurred in Tanjungharjo Village, Bojonegoro Regency. Morbidity rate for hypertension cases at Puskesmas Tanjungharjo is ranked first among non-communicable diseases and third among 10 diseases with the most sufferers in that area. Objectives: This study aims to analyze planning and evaluation of hypertension management program using PRECEDE-PROCEED approach in Tanjungharjo Village, Bojonegoro. Research Methods: The research was conducted using mix-methods study design with primary and secondary data. Preliminary study was conducted to obtain hypertension data in Tanjungharjo Village. The research was conducted on 54 PROLANIS participants in Tanjungharjo Village. Primary and secondary data analysis was conducted using PRECEDE-PROCEED framework. Results: The results of preliminary study show that respondents’ hypertension knowledge is low (75,9%). Analysis of respondents characteristics resulted that respondents were suitable for receiving hypertension programs. Analysis using PRECEDE-PROCEED framework shows the need for wider accessibility and more attractive programs. A program called “GERINDI POTENSI” was initiated with 3 sub-programs, namely Kelas Memasak Sehat Yuk (Kemayu) aimed at increasing knowledge regarding diet and healthy cooking methods for hypertension, Senam Lansia Anti Hipertensi (Selasi) aimed at increasing physical activity for hypertension, and Buku Rekap Skrining Kesehatan (Buku Rekan) aimed to summarize health examinations results of PROLANIS participants. Conclusion: : Planning and evaluation of hypertension programs in Tanjungharjo Village using PRECEDE-PROCEED approach resulted “GERINDI POTENSI” program which is suitable with needs and priority problems. Monitoring and evaluation has been conducted with results of achieving program indicators.